Literature Review: Analisis Profitabilitas Pelanggan - Aan Kanivia; Nadzma Adelia Putrie; Safani Anugrah; Icuk Rangga Bawono (JRAK: Journal of Accounting Research and Computerized Accounting, 2025)
One important factor in business continuity efforts (going concern) that companies need to pay attention to is the company's paradigm regarding customers. Companies often use methods such as Customer profitability analysis to identify and understand the involvement of each customer in the company's profits and revenue. This paper aims to analyze customer profitability which is important for decision making and company survival. This research uses a literature study methodology. The information used comes from various secondary sources and is then researched using qualitative data examination techniques. The results show that the application of customer profitability analysis can help companies manage customers who will provide benefits to the company, so that it can help in making strategic decisions and assessing the company's success. Customer profitability analysis helps companies identify the contribution of each customer to profits and customer performance to the company.